The determination of organic practice and adoption in sugarcane farming in Thailand - Kuldilok, Kulapa (Kasetsart Journal of Social Sciences, 2021)
Organic production at sugarcane farms facilitates increased food safety and environmental sustainability; however, the number of organic sugarcane farms in Thailand is still low. The purpose of this research is to determine organic practice standards and their adoption in sugarcane farming in Thailand. A purposive sample of 414 sugarcane farmers from Kanchanaburi and Suphanburi provinces using a non-probability technique and 30 certified organic sugarcane farmers from Nakhon Ratchasima was collected. Data were collected by conducting face-to-face interviews with individual respondents. The findings revealed that the most difficult organic practices are (1) informing the Organic Agriculture Certification Thailand (ACT) of any change in production (2) stopping the use of all chemical inputs for 1 year (3) no burning after harvest (4) cleaning all equipment before use and (5) record keeping for all of the process from the farm to the mill. The adoption results revealed that gender, the number of agriculture information channels, debt, land right certificates, asset value and organic training were significantly important factors in organic practice while sugarcane plantation experience, household labor, farm size and training from millers had no influence on adoption. It is recommended that employees organize additional practical training programs on organic standards, and organic certification should be simple to process and cost less. The ownership of land will support more organic practice. Moreover, the benefits of organic production should also be promoted to female sugarcane farmers. The government could also offer support to farmers in regard to loan repayments.